Pengaruh Motivasi dan Disiplin Kerja Terhadap Kinerja Karyawan : (Studi Kasus Pada PT. Albea Rigid Packaging Surabaya) - Siti Aisah; Yuri Triono (Universitas Nusantara PGRI Kediri, 2023)
PT Albea Rigid Packaging Indonesia is a halal cosmetic packaging manufacturer that must prepare its human resources in order to improve company performance in the cosmetic industry. The purpose of this study is to measure how much